Investigation of the relationship between apelin hormone response and some physiological parameters in enzootic bovine leukosis virus infected cattle - Sait, A; Bayraktar, B; Korkmaz, S; Genç, M; Bayraktar, S; Kotan, GC; Aydemir, Ş; Takma, Ç; Bülbül, AS; Aksakal, V; Tekce, E; Böyük Özcan, GB; et al. (Journal of the Hellenic Veterinary Medical Society, 2025)
Apelin is a hormone with lymphangiogenesis potential, associated with tumor growth and lymph node metastasis, and reported to stimulate tumor vascularization. This study, it was aimed to investigate the apelin hormone response depending on some physiological parameters (race, age and body condition score) in cattle with and without Enzootic Bovine Leukosis (EBL) infection. A total of 120 Simmental and Montofon cattle of different ages (<2, 2-8, and ≥8) and different body condition scores (<2, 3-3.5 and ≥4) comprised the animal material of the study. The apelin hormone level in serum was examined using the ELISA technique in blood samples taken from the neck vein (Vena jugularis) of animals. As a result of the analyzes made, When the mean serum Apelin (ng mL-1) values of BCS*EBL*Age*Race are examined, the highest values in terms of EBL ± are 2.77 ng mL-1 in Simmental cattle between 2-8 years of age with BCS=3- 3.5 while Montofon breed cattle 2.69 ng mL-1 was determined in cattle with BCS=3-3.5 in the age range of 8<. When the mean serum Apelin (ng mL-1) values in terms of EBL - are examined, the highest value is 2.24 ng mL-1 in Simmental cattle aged 2-8 years with BCS=3-3.5, while the highest value is 2.24 ng mL-1 in Montofon breeds 8< years old BCS=3- 3.5 in cattle 1.45 ng mL-1 was determined. As a result, the effect of apelin on hormone levels was demonstrated for the first time in cattle with or without EBL disease, depending on some physiological parameters (age, race and BCS). It is thought that Apelin hormone, which is characterized by neoplastic lymphocyte cell infiltrations in the lymphoreticular tissues of cattle and has a role in the regulation of tumor growth against EBL, a malignant tumoral disease, may contribute to the processes of eradication programs and the evaluated parameters may be useful in disease prevention and control strategies.